Remote Observation of Field Work on the Farm - Ju, Wendy; Mandel, Ilan; Weatherwax, Kevin; Takayama, Leila; Martelaro, Nikolas; Willett, Denis (2020)
ABSTRACT Travel restrictions and social distancing measures make it difficult to observe, monitor or manage physical fieldwork. We describe research in progress that applies technologies for real-time remote observation and conversation in on-road vehicles to observe field work on a farm. We collaborated on a pilot deployment of this project at Kreher Eggs in upstate New York. We instrumented a tractor with equipment to remotely observe and interview farm workers performing vehicle-related work. This work was initially undertaken to allow sustained observation of field work over longer periods of time from geographically distant locales; given our current situation, this work provides a case study in how to perform observational research when geographic and bodily distance have become the norm. We discuss our experiences and provide some preliminary insights for others looking to conduct remote observational research in the field. ABOUT THE AUTHOR/S Wendy Ju Cornell Tech wendyju@cornell.edu Wendy Ju is an Associate Professor in Information Science at the Jacobs Cornell Technion Institute at Cornell Tech. Her research focus lies on interaction with autonomous systems such as automobiles and robots. She graduated with her PhD in Mechanical Engineering, from Stanford University in 2008. Ilan Mandel Cornell Tech im334@cornell.edu Kevin Weatherwax UC Santa Cruz keweathe@ucsc.edu Leila Takayama UC Santa Cruz takayama@ucsc.edu Nikolas Martelaro Carnegie Mellon University nikmart@cmu.edu Denis Willett Cornell AgriTech deniswillett@cornell.edu New Future of Work 2020, August 3–5, 2020 © 2020 Copyright held by the owner/author(s).